Significant interactions for human development - Llanos Zuloaga, Martha (2019)
For human development, the role of human interactions and those involving the nature and objects from family, social, and school contexts is vital. This study offers a reflection on the relevance of significant interactions between adults and children, in particular, in a way that cognitive and socioemotional learning has an impact on children’s development. The author carries out a review after 20 years of the great topic of the adult’s inner child and the resilient capabilities of children and adults forged and consolidated in positive interactions. Two decades later, we must add the intervention of digital technology, which offers certain positive aspects for everyday learning, but can also considerably limit interaction and face-to-face communication, creative potential, and activities of social communication restricted to passive curiosity and exploration. In 1998, the question was: are the twentieth-century children, -nowadays parents- prepared for the twenty-first century children? This is still a valid question today and the concern also includes to find out how well parents are prepared and how much the voices of twenty-first century children are heard. This century has begun with high levels of violence, consumerism and materialism, and requires to make a stand for greater and better values and awareness to create valuable opportunities for childhood development both in Peru and in the world.